Efek Goal Commitment, Lingkungan Litigasi, dan Kepercayaan Pada Penerimaan Auditor Atas Metode Pilihan Klien (Studi Empiris Pada KAP Jakarta) - Zulfikar, Rudi; Rosiana, Rita; Romauli, Kristin (Jurusan Akuntansi Politeknik Negeri Padang, 2013)
The purpose of this research is to examine three factors that affect audit decision such as goal commitment, litigation environment and trust on auditor’s acceptance of the client’s preferred methods. Data were collected through questionaires using purposive sampling method. Samples were selected from accounting firms which were listed on Directory of Ikatan Akuntan Publik Indonesia for 2013 period in Jakarta. Out of the 150 questionnaires sent, the final analysis was based on the response from 109 auditors (72.67%). Moreover, data analysis uses Structural Equation Model (SEM) by using AMOS (Analysis of Moment Structures) version 21.0. The results of this research reveal that (1) goal commitment is positively related to the auditor’s acceptance of the client’s preferred method, (2) litigation environment is negatively related to the auditor’s acceptance of the client’s preferred method, and (3) trust is negatively related to the auditor’s acceptance of the client’s preferred method